Quality control for engineers. (August 2018) - Lee, Matt
Abstract : In 2011 'Quality Control Measurements for digital X-ray detectors' was published by Marshall, Mackenzie and Honey. These outlined a series of objective measurements that could be done in a short period of time and with limited equipment that would pick up most foreseeable issues with image quality. Obtaining these images could be done by service engineers on routine service visits thereby tripling the frequency with which certain measurements are taken (potentially reducing the number of patients imaged on equipment that has failed a QC test). A program written in Matlab for engineers will be presented which analyses; uniformity, SNR, STP curve, dark noise, image lag (ghosting), MTF, NPS and DQE. Initial results compared to manufacturer specifications for both mammography and conventional DR imaging detectors will be presented. Objective image quality measurements benefit from highly reproducible and not operator dependent, which will hopefully increase confidence in the validity of these reports. The algorithms used in the program and potential collaboration will be discussed as well as pitfalls- particularly around NPS measurements.